Altered plasma proteins released from platelets and endothelial cells are associated with human patent ductus arteriosus. Issue 5 (27th November 2018) - Hou, Hai‐Tao; Xi‐Zhang,; Wang, Jun; Liu, Li‐Xin; Zhang, Jian‐Feng; Yang, Qin; He, Guo‐Wei
Abstract: Patent ductus arteriosus is the third most common congenital heart disease and resulted from the persistence of ductal patency after birth. Ductus arteriosus closure involves functional and structural remodeling, controlled by many factors. The changes in plasma protein levels associated with PDA closure are not known. Here we for the first time demonstrate six key differential plasma proteins in human patent ductus arteriosus patients using proteomic technology and present a model to illustrate the constriction and closure of ductus arteriosus. Differentially expressed proteins were analyzed by using isobaric tags for relative and absolute quantification and validated by enzyme‐linked immunosorbent assay in new samples. The proteomic data have been deposited to the ProteomeXchange Consortium via the PRIDE partner repository with the data set identifier PXD008568. We found 74 upregulated and 98 downregulated proteins in the plasma of patients with PDA. Five decreased proteins (platelet factor 4, fibrinogen, von Willebrand factor, collagen, and mannose binding lectin‐associated serine protease‐2) and one increased protein (fibronectin) may increase the risk of patent ductus arteriosus. Those proteins are closely related to platelet activation and coagulation cascades, complement mannan‐binding‐lectin, and other systemic signaling pathways. Our findings for the first time indicate that the differential proteins involved in different pathways may play key roles in the nonclosure of the ductus arteriosus in humans and may be developed as biomarkers for diagnosis. All those findings may be served as the basis of understanding the etiology and pathogenesis of patent ductus arteriosus. Abstract : Ductus arteriosus closure involves functional and structural remodeling, controlled by many factors and we for the first time demonstrate six key differential plasma proteins in human patent ductus arteriosus patients using proteomic technology and present a model to illustrate the constriction and closure of ductus arteriosus. Those proteins are closely related to platelet activation and coagulation cascades, complement mannan‐binding‐lectin, and other systemic signaling pathways. Our findings for the first time indicate that the differential proteins involved in different pathways may play key roles in the nonclosure of the ductus arteriosus in humans and may be developed as biomarkers for diagnosis. All those findings may be served as the basis of understanding the etiology and pathogenesis of patent ductus arteriosus.